Bio-Catalytic Structural Transformation of Anti-cancer Steroid, Drostanolone Enanthate with Cephalosporium aphidicola and Fusarium lini, and Cytotoxic Potential Evaluation of Its Metabolites against Certain Cancer Cell Lines - Choudhary, M. Iqbal; Siddiqui, Mahwish; Atia-tul-Wahab,; Yousuf, Sammer; Fatima, Narjis; Ahmad, Malik S.; Choudhry, Hani (Frontiers in Pharmacology, 2017)
In search of selective and effective anti-cancer agents, eight metabolites of anti-cancer steroid, drostanolone enanthate (1), were synthesized via microbial biotransformation. . Enzymes such as reductase, oxidase, dehydrogenase, and hydrolase from Cephalosporium aphidicola, and Fusarium lini were likely involved in the biotransformation of 1 into new metabolites at pH 7.0 and 26 °C, yielding five new metabolites, 2α-methyl-3α,14α,17β-trihydroxy-5α-androstane (2), 2α-methyl-7α-hydroxy-5α-androstan-3,17-dione (3), 2-methylandrosta-11α-hydroxy-1,4-diene-3,17-dione (6), 2-methylandrosta-14α-hydroxy-1,4-diene-3,17-dione (7), and 2-methyl-5α-androsta-7α-hydroxy-1-ene-3,17-dione (8), along with three known metabolites, 2α-methyl-3α,17β-dihydroxy-5α-androstane (4), 2-methylandrosta-1,4-diene-3,17-dione (5), and 2α-methyl-5α-androsta-17β-hydroxy-3-one (9), on the basis of NMR, and HREI-MS data, and single-crystal X-ray diffraction techniques. Interestingly, C. aphidicola and F. lini were able to catalyze hydroxylation only at alpha positions of 1. Compounds 1-9 showed a varying degree of cytotoxicity against HeLa (human cervical carcinoma), PC3 (human prostate carcinoma), H460 (human lung cancer), and HCT116 (human colon cancer) cancer cell lines. Interestingly, metabolites 4 (IC50 = 49.5 ± 2.2 µM), 5 (IC50 = 39.8 ± 1.5 µM), 6 (IC50 = 40.7 ± 0.9 µM), 7 (IC50 = 43.9 ± 2.4 µM), 8 (IC50 = 19.6 ± 1.4 µM), and 9 (IC50 = 25.1 ± 1.6 µM) were found to be more active against HeLa cancer cell line than the substrate 1 (IC50 = 54.7 ± 1.6 µM). Similarly, metabolites 2 (IC50 = 84.6 ± 6.4 µM), 3 (IC50 = 68.1 ± 1.2 µM), 4 (IC50 = 60.4 ± 0.9 µM), 5 (IC50 = 84.0 ± 3.1 µM), 6 (IC50 = 58.4 ± 1.6 µM), 7 (IC50 = 59.1 ± 2.6 µM), 8 (IC50 = 51.8 ± 3.4 µM), and 9 (IC50 = 57.8 ± 3.2 µM) were identified as more active against PC-3 cancer cell line than the substrate 1 (IC50 = 96.2 ± 3.0 µM). Metabolite 9 (IC50 = 2.8 ± 0.2 µM) also showed potent anticancer activity against HCT116 cancer cell line than the substrate 1 (IC50 = 3.1 ± 3.2 µM)., In addition, compounds 1-7 showed no cytotoxicity against 3T3 normal cell line, while compounds 8 (IC50 = 74.6 ± 3.7 µM), and 9 (IC50 = 62.1 ± 1.2 µM) were found to be weakly cytotoxic.